Stark control of electrons along nanojunctions - Chen, Liping; Zhang, Yu; Chen, GuanHua; Franco, Ignacio (Nature communications, 2018)
Ultrafast control of currents on the nanoscale is essential for future innovations in nanoelectronics. Recently it was experimentally demonstrated that strong non-resonant few-cycle 4 fs laser pulses can be used to induce phase-controllable currents along gold–silica–gold nanojunctions in the absence of a bias voltage. However, since the effect depends on a highly non-equilibrium state of matter, its microscopic origin is unclear and the subject of recent controversy. Here we present atomistically detailed (time-dependent non-equilibrium Green’s function) electronic transport simulations that recover the main experimental observations and offer a simple intuitive picture of the effect. The photoinduced currents are seen to arise due to a difference in effective silica-metal coupling for negative and positive field amplitudes induced by lasers with low temporal symmetry. These insights can be employed to interpret related experiments, and advance our ability to control electrons in matter using lasers. Strong non-resonant few-cycle laser pulses can be used to induce ultrafast phase-controllable currents along nanojunctions but the microscopic origin is unclear. Here, the authors present time-dependent quantum transport simulations that recover the experimental observations and offer an intuitive picture of the effect.